The Effect of Theory of Mind Training on Social Skills Improvement in Intellectually Disabled Students - mahboub bakhshi-Barzili; Ma'soumeh Pourmohammadreza-Tajrishi; narges Adib-Sereshki; esmat mikaeili (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The development of theory of mind is considered as one aspect of social cognition by researchers and have attracted their attention in recent years. The purpose was to determine the effect of theory of mind training on social skills in male students with intellectual disability in Meshkinshahr City. Materials & Methods: In present experimental study, pretest-posttest design with control group were used. All intellectually disabled male students (aged 8-12 years old) who educating in Meshkinshahr (43 individuals) answered to theory of mind tests. Students who could not pass the tests (39 individuals) selected as a sample and their teachers completed Social Skills Rating Scale (SSRS Gresham & Elliot, 1990) for them. They assigned randomly to experimental and control groups. Experimental group participated in 8 training sessions (for 2 weeks, 30 minutes per session). After last session, theory of mind tests and SSRS administered for all subjects again. Data were assesed with analysis of covariance.  Results: Analysis of covariance showed that experimental group performed better than control group in social skills index, cooperation and self-control components significantly (P=0.001). But, two groups were not significantly different in assertion component.  Conclusion: theory of mind training leads to improvement in social skills and its components of intellectually disabled students and will guarantee their success on these areas in adulthood.